The Regional Self-Organizing Potential in Sustainable Agriculture: An Analysis of Co-operative Agreements on Nitrate Pollution by means of Rough Set Methods - Peter Nijkamp; Katrin Oltmer (Tinbergen Institute, 2004)
This study addresses the achievements of cooperative agreements in sustainable agriculture policy. After an economic analysis of multi-actor choice situations, it focuses the attention on the self-organizing potential of regional market parties in order to comply with environmental policy objectives. The empirical application concerns voluntary agreements among farmers in Bavaria regarding intensified efforts to reduce nitrate pollution of drinking water. By means of new variants of artificial intelligence methods based on rough set analysis, a systematic investigation of success factors of such strategies is achieved.
Keywords: Q18; Q24; Q53; 330; Agriculture; co-operative agreements; nitrate pollution; rough set analysis; Landwirtschaft; Umweltbewusstsein; Gewässerschutz; Düngemittel; Bayern